Reducing the Risk of Groundwater Contamination by Improving Drinking Water Well Condition - Hickman, John S.; Herbel, Kevin L.; Rogers, Danny H.; Powell, Morgan (My University, 1998)
Whether a well taps water just below the ground or hundreds of feet deep, its location on top of the ground is a crucial safety factor. Locating a well in a safe place takes careful planning and consideration of such factors as where the well is in relation to surface drainage and groundwater flow. A well downhill from a livestock lot, a leaking tank or a failing septic system runs a greater risk of contamination than a well on the uphill side of these pollution sources. The general rule for protecting the water supply is to keep a well upslope and as far as possible from potential sources of contamination.
EP33_1998-08
Keywords: EP33; Environment and Natural Resources; Equipment and Structures; Health and Safety; EP